A Hierarchical CuO Nanowire@CoFe-Layered Double Hydroxide Nanosheet Array as a High-Efficiency Seawater Oxidation Electrocatalyst - Xiya Yang; Xun He; Lang He; Jie Chen; Longcheng Zhang; Qian Liu; Zhengwei Cai; Chaoxin Yang; Shengjun Sun; Dongdong Zheng; Asmaa Farouk; Mohamed S. Hamdy; et al. (Molecules, 2023)
Seawater electrolysis has great potential to generate clean hydrogen energy, but it is a formidable challenge. In this study, we report CoFe-LDH nanosheet uniformly decorated on a CuO nanowire array on Cu foam (CuO@CoFe-LDH/CF) for seawater oxidation. Such CuO@CoFe-LDH/CF exhibits high oxygen evolution reaction electrocatalytic activity, demanding only an overpotential of 336 mV to generate a current density of 100 mA cm−2 in alkaline seawater. Moreover, it can operate continuously for at least 50 h without obvious activity attenuation.